Composite Coatings of AMg3 Alloy Formed by a Combination of Plasma Electrolytic Oxidation and Fluoropolymer Spraying - Dmitry V. Mashtalyar; Konstantine V. Nadaraia; Igor M. Imshenetskiy; Evgeniy A. Belov; Mariia S. Gerasimenko; Sergey L. Sinebryukhov; Sergey V. Gnedenkov (Molecules, 2023)
This paper presents the results of an investigation of the changes in the corrosion, wear resistance, and wettability of composite coatings formed on the AMg3 alloy through plasma electrolytic oxidation (PEO) and subsequent spraying with an organofluorine polymer. The evaluation of the electrochemical properties of the composite layers revealed a decrease in the corrosion current density compared with the PEO coating (from 3.8 × 10−8 to 3.1 × 10−11 A/cm2). The analysis of the wear resistance of composite coatings established that the application of this type of coating reduced the wear of the samples by two orders of magnitude when compared with the PEO layer. Using the contact-angle measurement, it was found that with an increase in the number of polymer spray applications, the wettability of coatings decreased, so the contact angle for the composite coating with triple fluoropolymer application increased by 134.3° compared to the base PEO coating.